Eating Habits and Age at Menarche in Junior High School Female Students in DKI Jakarta Province in 2023: Kebiasaan Makan dan Usia Menarche pada Siswi Sekolah Menengah Pertama di Provinsi DKI Jakarta Tahun 2023 - Christanti, Stefani; Syafiq, Ahmad; Fikawati, Sandra (Amerta Nutrition, 2024)
Background: The trend of decreasing age at menarche to be younger can impact on physical and psychological health. Nutritional factors, including dietary habits, are important and modifiable predictors of menarche age. Objectives: To analyze dietary habits' effect on the age at menarche among junior high school students in DKI Jakarta by considering nutritional status, level of physical activity, psychological state, and socio-economic conditions. Methods: A cross-sectional study was conducted on 420 female students from 15 junior high schools in DKI Jakarta in May 2023. Dietary habits were measured using the Semi-Quantitative Food Frequency Questionnaire, while the age at menarche and other factors were obtained through interviews, questionnaires, weight and height measurements. Data were statistically analyzed through the T Test, Mann Whitney Test, Chi-Square Test, as well as Multivariate Logistic Regression Test. Results: The age at menarche ranged from 8.92 to 14.33 years, with an average of 11.74 years. Respondents tend to consume carbohydrates, fat, protein, sugar, and salt â‰¥100% of Recommended Dietary Allowances (RDA). However, 70.7% of respondents had the habit of consuming dietary fiber <100% of RDA. Low fiber diet (<29 g/day) is significantly related to earlier menarche age based on the T-test (p-value=0.006) and logistic regression test after controlling for dietary habits of fat, protein, and salt (p-value=0.047) with OR=0.569 (95% CI 0.325-0.993). The analysis also found that nutritional status and socio-economic conditions were associated with menarche age. Conclusions: Low fiber diet has a 1.76 times chance of earlier menarche than high fiber diet. A balanced nutritional intake, including vegetables and fruits as source of fiber, is recommended to support adolescent growth and development, puberty, and general health.